2022
DOI: 10.3389/fchem.2022.915648
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends in Natural Biopolymers in the 21st Century: A Scientometric Review

Abstract: Since the 21st century, natural biopolymers have played an indispensable role in long-term global development strategies, and their research has shown a positive growth trend. However, these substantive scientific results are not conducive to our quick grasp of hotspots and insight into future directions and to understanding which local changes have occurred and which trend areas deserve more attention. Therefore, this study provides a new data-driven bibliometric analysis strategy and framework for mining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…According to the Intergovernmental Panel on Climate Change (IPCC), biopolymers could make a significant contribution to limiting global warming to 1.5 degrees Celsius by removing up to 20% of CO 2 [ 17 ]. Recent research trends on natural biopolymers have shown positive growth in the case of long‐term global sustainable development strategies [ 18 ]. Biopolymers have received a lot of attention because of their unique properties, low cost, biodegradability, non‐toxicity, biocompatibility economic sustainability, ease of availability, and wide range of applications [ 19 ].…”
Section: Biopolymers: Sustainable Green Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Intergovernmental Panel on Climate Change (IPCC), biopolymers could make a significant contribution to limiting global warming to 1.5 degrees Celsius by removing up to 20% of CO 2 [ 17 ]. Recent research trends on natural biopolymers have shown positive growth in the case of long‐term global sustainable development strategies [ 18 ]. Biopolymers have received a lot of attention because of their unique properties, low cost, biodegradability, non‐toxicity, biocompatibility economic sustainability, ease of availability, and wide range of applications [ 19 ].…”
Section: Biopolymers: Sustainable Green Materialsmentioning
confidence: 99%
“…It is in an explosive growth stage from 2018 to 2021, with a total of 1746 articles published, an average annual publication volume of around 437 articles, a total of 76,852 citations, and an average annual citation of around 19,213 times. The number of articles published each year is increasing with higher number of citations [ 18 ]. On the other hand, the biopolymer market size was 6.95 billion USD in 2018 and is expected to reach 14.92 billion USD by 2023, at a compound annual growth rate (CAGR) of 16.5% [ 39 ].…”
Section: Biopolymers: Sustainable Green Materialsmentioning
confidence: 99%
“…As previously discussed, nature is a crucial source of readily available heterogeneous HBDs due to the abundance of biopolymers rich in −NH and −OH groups . In particular, cellulose and hemicellulose (containing only aliphatic −OH groups) are the most abundant biopolymers followed by chitosan (containing both aliphatic −OH and −NH 2 groups) and lignin (the most abundant biopolymer containing phenolic −OH groups along with aliphatic −OH groups) . Compared to the latter biopolymers, melanin and tannins are relatively less abundant but they are rich in phenolic hydroxy groups which are highly active HBDs in the cycloaddition of CO 2 to epoxides. , Selected examples to highlight the progress in the application of such HBDs under mild reaction conditions are briefly detailed below.…”
Section: Monofunctional Polymersmentioning
confidence: 99%
“…The development of bibliometric tools such as the R package "Bibliometrix" (Arruda et al, 2022) and the software packages "CiteSpace" (Liu et al, 2022) and "VOSviewer" (Huang et al, 2022) makes visual analysis of documents more convenient. These programs have been widely used in various fields, such as medicine (Youn et al, 2022), climate (Han et al, 2022), materials science (Sun et al, 2022), and others. In recent years, studies have indicated that using 3D printing bioink to treat bone tissue defects has good prospect, however bibliometric evaluation of this valuable field is currently lacking.…”
Section: Advantages Of Bibliometric Analysismentioning
confidence: 99%